(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This dance/educational study aims at understanding the impacts generated from the pedagogical practice with Traditional Northeastern Dances at the School for Reference in Middle School Sizenando Silveira (EREM Size), in the year 2022. Therefore, we organized the text based on two theoretical foundations, which are: (1) The EREM Size, the Curriculum of Pernambuco and the Traditional Northeastern Dances, and (2) Formation of authors in Dance: possibilities based on the repertoires of the Traditional Northeastern Dances. Then, we reflected about the teaching-learning processes with the mentioned dances at school and their implications in the teacher and in the students. With this work, we realize how much the repertoires of these dances are sources of knowledge and can/should be used as a means for a transgressive education, which begins in the body and its social markers.